Honor bound - Griffin, W. E. B. frey50; Hill, Dick.; Media Books Audio Publishing (Englewood Cliffs, NJ : Media Books Audio Pub., 1994)
It's 1942. A Marine aviator, an Army paratrooper and demolitions expert, and a non-com radio man are on an impossible mission for the OSS-to sabotage the resupply of German ships and submarines-by any means necessary!
At head of title: Media Books presents.
Abridged.
Read by Dick Hill.
Keywords: United States. -- Marine Corps -- History; World War, 1939-1945; Talking books; United States -- History, Military -- 20th century; Historical fiction; War stories